TINGKAT OPINI PENYANDANG TUNARUNGU SISWA SLB DI DAERAH JAKARTA BARAT TERHADAP BAHASA ISYARAT DALAM BERITA DI STASIUN TV CNN INDONESIA - Rofiano Hanif Setiawan (2023)
This research is motivated by communication issues faced by the hearing-impaired community, which are still prevalent in Indonesia. These issues include the limited ability of hearing-impaired individuals to communicate, especially with those who are not hearing-impaired, and difficulties in receiving information through television media. Therefore, there is a need to address the effectiveness of sign language communication in news programs on TV stations for the hearing-impaired community. This study aims to determine the effectiveness of sign language communication in news broadcasts on TV stations for hearing-impaired students in SMPLB schools in West Jakarta. The study used a quantitative method with an explanatory causal research design, using non-probability sampling to collect data through structured questionnaires on the study population. The population sample included 50 students, representing the total number of hearing-impaired students in SMPLB schools in West Jakarta. Data analysis techniques used in the study included correlation tests, determination tests, model summaries, and ANOVA tests. Based on the study, it can be concluded that sign language in news programs on TV stations has an impact on the effectiveness of sign language communication. This conclusion is supported by the results of the correlation tests conducted in the study.